Survivorship and prostate cancer: the TrueNTH Supported Self‐Management programme. Issue 1 (January 2016) - Madaan, Sanjeev; Reekhaye, Abhishek; McFarlane, Jonathan
Abstract : With the rapid increase in the number of new prostate cancer diagnoses and the growing number of cancer survivors, there is a need for a new model of survivorship care to address the holistic needs of our patients. The TrueNTH initiative, launched by the Movember Foundation, is set to markedly change the survivorship experience of men with prostate cancer and has the potential to make a big impact on their lives.